The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1017/jfm.2011.219
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of spatially developing turbulent boundary layers with uniform blowing or suction

Abstract: Direct numerical simulation (DNS) of spatially developing turbulent boundary layer with uniform blowing (UB) or uniform suction (US) is performed aiming at skin friction drag reduction. The Reynolds number based on the free stream velocity and the 99 % boundary layer thickness at the inlet is set to be 3000. A constant wall-normal velocity is applied on the wall in the range, −0.01U ∞ 6 V ctr 6 0.01U ∞ . The DNS results show that UB reduces the skin friction drag, while US increases it. The turbulent fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
106
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 42 publications
(49 reference statements)
23
106
3
Order By: Relevance
“…This indicates that uniform blowing enhances the turbulence intensities, whereas uniform suction suppresses the turbulence intensities. These opposite effects are similar to those observed in incompressible flow [4]. In addition, uniform blowing reduces the mean density and increases the mean temperature, whereas uniform suction increases the mean density and reduces the mean temperature.…”
Section: Dear Editorssupporting
confidence: 73%
See 1 more Smart Citation
“…This indicates that uniform blowing enhances the turbulence intensities, whereas uniform suction suppresses the turbulence intensities. These opposite effects are similar to those observed in incompressible flow [4]. In addition, uniform blowing reduces the mean density and increases the mean temperature, whereas uniform suction increases the mean density and reduces the mean temperature.…”
Section: Dear Editorssupporting
confidence: 73%
“…Direct numerical simulations (DNSs) provide accurate data that can be used to study the underlying physics of drag reduction. In a recent DNS [4] of an incompressible spatially developing turbulent boundary layer with uniform blowing or suction applied on the wall, the drag reduction mechanism was quantitatively explained by the Fukagata, Iwamoto and Kasagi (FIK) identity [5]. Compared with incompressible flows, far fewer studies have been reported for high-speed (hypersonic) flows.…”
Section: Dear Editorsmentioning
confidence: 99%
“…The second-order accurate finite difference method is used in the LES code, which is based on the direct numerical simulation (DNS) code of Kametani and Fukagata (2011). A staggered grid system, where the velocities are defined on the cell surface, while the pressure and the eddy viscosity are located at the cell centre, is used in the present model.…”
Section: Numerical Set-upmentioning
confidence: 99%
“…The flow field of a turbulent boundary layer at a low Reynolds number (with friction Reynolds number of Re τ = u τ δ/ν ≈ 180, which corresponds to Re = U ∞ δ/ν ≈ 3000), originally used in the DNS code of Kametani and Fukagata (2011), was used as the initial field. The non-dimensional timestep tU ∞ /δ was set to be 1×10 −3 .…”
Section: Numerical Set-upmentioning
confidence: 99%
“…The uniform suction improves the stability of the laminar boundary layer: the transition will be delayed and the overall friction drag will be reduced due to the extended laminar region (Joslin, 1998). In contrast, the uniform blowing is known to reduce the drag in the fully-turbulent regime, as studied, e.g., by Kametani and Fukagata (2011). Therefore, a combination of suction and blowing is expected to be effective for flows involving laminar-turbulent transition, such as the flow around an airfoil, by delaying the transition near the trailing edge and by reducing the turbulent drag in the post-transition (i.e., fully-turbulent) region (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%